Public Relations Strategy for School Development at PKBM Permata Sunnah: Strategi Hubungan Masyarakat untuk Pengembangan Sekolah di PKBM Permata Sunnah - Napitupulu, Lilis Suriyani; Fahyuni, Eni Fariyatul (Indonesian Journal of Cultural and Community Development, 2025)
General Background: Public relations management is essential in improving institutional image and community trust in non-formal education. Specific Background: PKBM Permata Sunnah Sidoarjo implements Islamic-based education but lacks structured public relations management to communicate its achievements. Knowledge Gap: Few studies address how PR strategies influence the visibility and sustainability of Islamic community learning centers. Aims: This research aims to formulate a school development plan based on public relations strategies at PKBM Permata Sunnah. Results: The study found that the institution has strong academic and religious programs but limited promotion and coordination, leading to low public awareness. The SWOT analysis indicates strengths in curriculum and teacher competence, but weaknesses in communication and media utilization. Novelty: The research integrates PR strategy with Islamic educational management to propose a comprehensive model for visibility improvement and institutional growth. Implications: Establishing a dedicated PR division, training communication staff, and using digital media are crucial steps for enhancing the institution’s public image and sustainability. Highlights: PR strategy is key to institutional branding. Curriculum quality must align with outreach efforts. Digital communication supports educational sustainability.